SPORTS ARENA AND ENTERTAINMENT DESIGN - Sinabariba, Darwin; Lubis, Syamsulsyah; Giatwin, Giatwin (ASTONJADRO, 2021)
The city of Binjai is considered to have a strategic position as a trading city because it is located on the cross-Sumatra route that connects Medan City, Langkat Regency, and the Province of the Special Region of Aceh. Observers consider that businessmen are looking at this city to invest their capital in various business opportunities that are open. The design of the Binjai Business Hotel is intended to fulfill the needs of business hotels to anticipate the arrival of domestic and foreign tourists to Binjai City, for business activities. The Business Hotel in East Binjai consists of rooms equipped with various facilities to accommodate the needs of business people including; business center, private meeting room, and convention hall. The building design is the embodiment of needs and location analysis which is a building located in the city center with a modern architectural theme.